The Cancer Observatory of Cali, a priority (Colombia Medica, 2018)
In the last issue of Colombia Médica, the Cali Population Registry of Cancer (RPCC, for its initials in Spanish) documented that important advances in cancer control have been achieved (https://www.ncbi.nlm.nih.gov/pmc/articles/PMC6018818/). Mortality due to this group of diseases has decreased significantly during the last 25 years, thanks to the partial control of cancers related to infectious agents (stomach and cervix) and cancers associated with tobacco consumption (lung, bladder, oral cavity). However, there is less control of cancers related to screening activities (breast, prostate and colorectal), and hematolymphoid tumors that have successful treatment options with chemotherapy. As a result, cancer survival in children and adults is 20 percentage points below that observed in Europe and the United States 1.One strategy to improve the indicators is the creation of a cancer observatory in the city. Health observatories are conceived as smart, proactive, dynamic, synchronic and participatory systems that generate knowledge for the formulation of policies and strategies that allow to impact, in a positive way, the social determinants of health (2). With this perspective and in congruence with the technical line of health observatories given by the Ministry of Health and Social Protection, it is necessary to generate strategies; to have articulation spaces; and to integrate sources of information, which in addition to being standardized and synchronized, facilitate the monitoring and identification of trends in the behavior of events, and the understanding and explanation of the health situation of the population based on complex analyses of inequalities and health vulnerabilities 2.